The physical characteristics underpinning performance of wheelchair fencing athletes: A Delphi study of Paralympic coaches - Villiere, A.; Mason, B.; Parmar, N.; Maguire, N.; Holmes, D.; Turner, A. (Journal of Sports Sciences, 2021)
Wheelchair fencing (WF) is a Paralympic sport which is practised by athletes with physical disabilities and is classified into three categories according to the degree of activity limitation the impairment causes in the sport. All Paralympic sports are requested to develop their own evidence-based classification system to enhance the confidence in the classification process; however, this is yet to be achieved in WF. Research within WF is scarce; therefore, the aim of this study was to reach expert consensus on the physical characteristics that underpin performance of athletes competing in the sport as this is known as one of the initial steps required to achieve an evidence-based classification system. Sixteen Paralympic WF coaches were invited to take part in a three-round Delphi study, with experts drawing consensus on qualities of speed, strength, power, flexibility and motor control of the trunk and fencing arm being associated with increased athletic success. The required qualities of the non-fencing arm led to diverging opinions across the expert panel. This study provides clear guidance of the physical qualities to be developed to maximize athletic performance while also providing the initial framework to guide future WF classification research.